Friedmann equations in modified gravity theories f(R) - Villegas , Fulgencio (2021)
In this work, the deduction of Friedmann's equations is presented in the context of modified gravity theories f(R); it has been considered to present them as a function of the constant k associated with the curvature of the hypersurface. To deduce it, a revision of the Lagrangian formulation of General Relativity and the modified gravity theories f (R) as well as the deduction of the field equation in the environment of the theories f(R) is previously made.